Natural exposure to Chikungunya virus in golden-headed lion tamarin (Leontopithecus chrysomelas, Kuhl, 1820) from non-protected areas in southern Bahia, Brazil: Implications and significance. - Sofía Bernal-Valle; María Angélica Monteiro de Mello Mares-Guia; Filipe Vieira Santos de Abreu; Fabrício Souza Campos; Cirilo Henrique de Oliveira; Antônio Victor Veloso Ramos; Reizane Pereira Lordelo; Kristel De Vleeschouwer; Leonardo de Carvalho Oliveira; Hllytchaikra Ferraz Fehlberg; Ana Maria Bispo Filippis; Bergmann Morais Ribeiro; et al. (PLoS Neglected Tropical Diseases)
Chikungunya virus (CHIKV) is primarily associated with non-human-primates (NHPs) in Africa, which also infect humans. Since its introduction to Brazil in 2014, CHIKV has predominantly thrived in urban cycles, involving Aedes aegypti mosquitoes. Limited knowledge exists regarding CHIKV occurrence and implications in rural and sylvatic cycles where neotropical NHPs are potential hosts, from which we highlight Leontopithecus chrysomelas (Kuhl, 1820), the golden-headed lion tamarin (GHLT), an endangered species endemic to the Atlantic Forest (AF) in Southern Bahia State, Brazil. The present study investigated wild GHLT groups across two municipalities, Ilhéus and Una, Bahia. Surveys were conducted in three groups within cocoa agroforests (cabrucas) in Ilhéus, and four groups in anthropized forest and agroforestry fragments in Una, between 2021 and 2022. Thirty-two GHLT specimens were captured and chemically immobilized, examined and submitted to blood sample collection; nine specimens were later recaptured in 2022, totaling 41 samples. CHIKV viremia was not detected in any specimens (as assayed by RT-qPCR). Plaque reduction neutralization test (PRNT90) detected CHIKV antibodies in two (6.3%) GHLTs, with 10-20 antibody titers. Seroprevalence in 2021 was 5.6% and in 2022 was 8.7% with an incidence of 4.5%, whereas, a male adult tested seropositive in both years, suggesting either natural re-exposure and antibody maintenance over time. All samples tested seronegative for Mayaro Virus. Eight mosquito species from the Culicidae family were collected, identified and assayed for CHIKV genomes, showing negative results. This study provides the first evidence of natural CHIKV exposure among free-living GHLTs in Brazil, emphasizing their susceptibility and potential role as reservoirs. These findings underscore the possible consequences of anthropic disturbances in the Brazilian AF, without a seroprevalence difference between non-protected forest formations, agroforest fragments and various mosaic farming landscapes in South Bahia, and highlight the importance of conservation efforts for this endemic and endangered primate species.